Estudo da extração de cromo hexavalente, pela técnica de membranas líquidas surfatantes, visando o tratamento de efluentes líquidos de curtumes - Vinicius Bayer (2005)
In the present work, it has been proposed to study the extraction of dichromate ions from an external phase (formed by potassium dichromate solution), using the surfactant liquid membrane technique (S.L.M). The main goal of this work is to reduce these species content in tanneries effluents. The following operational variables has been investigated: extractant concentration, surfactant concentration and modifier concentration presents in membrane phase, temperature, pH from the external phase (feed), permeation time and volumetric ratio of phases. The results have shown a high dependence of the extraction mechanism with pH of the external phase and temperature as well. The best operation condition obtained in this study was pH 1.25 at 35°C. The volumetric ratio was set in 9 : 2 : 1 (external phase : membrane phase : internal phase) due to good percentage of Cr6+ extraction and also for the maintenance of the stability of the system. According to the results obtained, L.S.M technique extraction has shown to be viable to remove hexavalent chromium ions, thus leading to high extraction percents (more than 98% from an external phase) and leaving a very diluted raffinate solution (less than 8 p.p.m of chromium). In these conditions, the influence of some operational variables has been investigated. Best levels for the removal of chromium was extractant concentration (tri-n-octylamine) of 2% p/p, surfactant concentration (ECA 4360) of 2% p/p, modifier concentration (1-Decanol) of 5% p/p, pH 1,25, permeation time of 5 min and temperature of 35°C. The reuse of loaded membrane phase was analyzed and it has been found a high extraction potential using recycled membranes in comparison to fresh membrane phase (around 98% of extraction) thus showing no significant losses of extractant. Finally, the system was operated in 2 cycles in order to evaluate the extraction capacity. Results have shown an extraction rate above 90%, giving chromium levels lower than 1 p.p.m, a very close value to the established one for the ambient agencies (maximum concentration is 0.5 p.p.m of hexavalent chromium present in tannery effluents).